Mediation in Malaysia: the law and practice - Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2010)
This book encompasses the law and practice of mediation in Malaysia. It covers a wide range of subject matters such as civil, criminal, commercial, matrimonial, labour, negligence claims and land disputes. It is a concerted effort by the main authors together with several contributors, both academic and professional, to highlight and discuss current issues affecting the law and practice of mediation. The content in the 32 chapters reflects the expertise of the authors and contributors in their respective fields. The underlying argument of the articles is that Alternative Dispute Resolution is the best and most expeditious form of resolving disputes. Although this book acknowledges that mediation has been employed in many areas; it nevertheless explores the relevance, options and future possibilities for amicable settlement in a broad range of sectors. Comparisons are made with the success rate of mediation in various countries. This is a testament that mediation should be embraced to simplify dispute resolution and reduce the delay, expense and backlog of cases pending in the Malaysian courts.